Perlindungan UMKM dalam Arus Perdagangan Internasional: Evaluasi Kewajiban Fair Competition bagi Negara Berkembang - Mufti, Muhammad Wildan (Media Hukum Indonesia (MHI), 2026)
This study analyzes how fair competition obligations within the WTO framework affect the position and protection of SMEs in developing countries. Although the WTO adopts the principle of non-discrimination to create equal competition, structural constraints faced by SMEs, such as limited capital, technology, and access to information, result in equality that is merely formal rather than substantive. International trade instruments such as the SCM Agreement, anti-dumping measures, non-tariff barriers, and the weak effectiveness of Special and Differential Treatment restrict the policy space of developing countries to protect their SMEs. This study also formulates a model for strengthening policies through affirmative approaches, including asymmetric competition law enforcement, subsidy reformulation, trade facilitation, and the integration of SMEs into global value chains and the digital economy. The findings demonstrate that comprehensive domestic and international regulatory reforms are necessary to ensure that fair competition truly creates substantive justice for SMEs.